The relationship between family support and lifestyle management in type 2 diabetes mellitus patients - Puji Astutik; Iwan Ardian; Nutrisia Nu’im Haiya (JOURNAL OF Community Health Issues, 2026)
Background: Adopting a healthy lifestyle is the primary solution for treating type 2 diabetes mellitus. Family support plays a crucial role as an external factor that can strengthen a patient's commitment to adopting a healthy lifestyle. The greater the family support, the better the self-care outcomes for patients with type 2 diabetes mellitus. Purpose: To determine the relationship between family support and lifestyle management in patients with type 2 diabetes mellitus. Method: The research method used was an observational cross-sectional approach. The study sample consisted of 200 diabetes mellitus patients who met the inclusion and exclusion criteria. The instruments used were the HDFSS and SDSCA questionnaires. Data analysis used the Chi-square test with a significance level of α = 0.05. Results: The results showed that the majority of respondents received good family support, and the majority of respondents' lifestyle management was in the good category. The Chi-square test showed a significant relationship between family support and lifestyle management (p = 0.001), indicating a significant relationship between family support and lifestyle management. Conclusion: There is a significant relationship between family support and lifestyle management.   Keywords: Diabetes Mellitus; Family; Lifestyle; Management; Support.